2020
DOI: 10.1111/cch.12814
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of the Ages and Stages Questionnaire® for school performance and school intervention in late preterm‐ and term‐born children

Abstract: Background: The new health supervision guidelines emphasize the importance of surveillance or a formal developmental screening test at 4 years, one of the most used tests is Ages & Stages Questionnaire. Nevertheless, there is still not enough evidence whether these tools will be useful to predict future school performance (SP). Objectives: The objectives of this study were to evaluate the Ages & Stages Questionnaire 3rd edition 48-month interval (ASQ3-48) translated to Spanish for predicting the need for schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…Of these, 32 publications met the inclusion criteria, corresponding to 10 cohort studies (Figure 1). The cohorts studied came from South America: Chile (19,27,36,37) and Colombia (26,38,39); Europe: Catalonia, Spain (40)(41)(42)(43), the Netherlands (28,(44)(45)(46)(47); France Poitiers and Nancy (48) and France Loire (49)(50)(51) and Norway (52)(53)(54); Asia: South Korea (55-57) and North India (58-62); Oceania: Australia (63).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 32 publications met the inclusion criteria, corresponding to 10 cohort studies (Figure 1). The cohorts studied came from South America: Chile (19,27,36,37) and Colombia (26,38,39); Europe: Catalonia, Spain (40)(41)(42)(43), the Netherlands (28,(44)(45)(46)(47); France Poitiers and Nancy (48) and France Loire (49)(50)(51) and Norway (52)(53)(54); Asia: South Korea (55-57) and North India (58-62); Oceania: Australia (63).…”
Section: Resultsmentioning
confidence: 99%
“…Another factor that could alter developmental trajectories is the interventions carried out in children, data not reported by any of the cohorts. Only in the study from Catalonia was there evidence of a lack of association between the evaluation carried out at the age of 4 years and referral to support programs in development ( 42 ). It is described that in real world, referral rates for early intervention among children with positive screens ranged from 10–86% ( 67 , 68 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if we look at the purpose of the developmental screening program itself, identifying and monitoring at‐risk children (including those who were incorrectly screened positive) gives more benefits that may lessen the future burden rather than losing the opportunity of missing the early intervention (resulting from those who were incorrectly screened negative). A recent study from Martínez‐Nadal et al found that ASQ‐3, specifically the 48‐month questionnaire, can predict school performance at 8–9 years old (Martínez‐Nadal et al, 2021). This opens the future possibility for follow‐up on the ASQ‐3 Indonesian version to determine the predictive validity of cognitive function and school performance at later ages.…”
Section: Discussionmentioning
confidence: 99%